Can Service Quality, Customer Trust and Price Affected the Decision to use Airport Services? - Putu Ayu Aryasih (Formosa Journal of Applied Sciences, 2023)
This study aims to determine the effect of service quality, consumer trust, and service prices on the decision to use the services of Joumpa PT. Gapura Angkasa Bali. The data collection technique uses a questionnaire that has been tested for validity and reliability, then various tests and analyzes are performed such as validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, and F test. The results of this study indicate that: (1) the service quality variable has a positive and significant effect on the decision to use services, (2) the customer trust variable has a positive and significant effect on the decision to use services, (3) the service price variable has a positive and significant effect on the decision to use the service.